Analysis Of Factors Affecting Community Participation In Waste Bank - Iman Hilman; Edi Jatmika; Supriyanto Supriyanto (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
The objective of this research is to determine the factors that influence community participation in waste banks. This objective was chosen because as a community movement, the sustainability of waste banks is largely determined by the participation of the community as its customers. The research was conducted quantitatively. The data collected is primary data obtained through interviews with respondents who are members of the Macodes waste bank located in Kedung Waringin Village, Tanah Sareal District, Bogor City. There were 30 respondents selected using simple random sampling. Data were analyzed using correlation and regression methods. There are 3 (three) factors that are thought to influence community participation in waste banks, namely understanding about waste, the economic benefits of waste banks, and professional and accountable management. The research results show that professional and accountable management is a factor that influences community participation. The other factors are the initial factors or drivers for the community to join as waste bank customers. The implication of this research is to ensure the sustainability of waste banks through community loyalty towards waste banks by having professional and accountable waste bank management. For this reason, it is necessary to provide guidance to waste bank managers.